PERIPHERAL’STATE RESPONSIBILITY UNDER GLOBALIZATION VS SOCIAL EXCLUSION AND SUSTAINABILITY: A CHALLENGE FOR MEXICO AND LATIN AMERICA IN CURRENT CENTURY - Luis-Pineda, Octavio (Seven Editora, 2025)
The majority of peripheral (and emerging) economies such as Mexico and other countries in Latin America and some other in peripheral regions around the world have undergone during the last four decades, socioeconomic, political, and environmental woes triggered not only by recurrent international financial crises in world markets, but also stemming from their long-time structural social, economic, and political problems such as unemployment, poverty, malnutrition, margination, income maldistribution, corruption and some unexpected temporary phenomenon such as the pandemic, which have entailed and inflicted a huge unprecedented social and economic costs both to peripheral but also developed economies, along to a host of externalities, producing social and environmental costs vis-a-vis the advent of globalization and trade liberalization and the concomitant increase of international trade between Mexico and the rest of the world, particularly between Mexico and its trade partners, under UMSCA treaty, namely, United States, and Canada. Under this context, it is worth mentioning the lack of a long-term strategy from most peripheral economies to not overlooking their States’ responsibility to promote long-term strategies aiming at curtailing the historically unbalanced growth pattern they have observed through time such as growing unemployment, income maldistribution, and notoriously, unsustainable handling of their natural resources along with other externalities. This article aims to highlight the fact that under today’s current global context, it comes out manifest a clear lack of long-term commitment from their States to implement strategies aiming to balance the binomial economic growth well-being under a sustainable framework in most peripheral economies, among manifold factors and particularly the pervasive presence and influence of international hegemonic institutions such as the World Bank, IMF in major economies, in Latin America and elsewhere throughout the periphery which has undermined the efforts of democratic governments to shift the current neoliberal-oriented-policies to maximize profit-at-all-cost strategies which have undermined population’s social wellbeing and sustainability prevailing throughout the periphery by another alternative one, a more socially inclusive and sustainably oriented strategy. One committed to paralleling fostering, economic growth and the people’s well-being in a country. Such a model currently prevails in some advanced socially inclusive economies (Scandinavian countries, Switzerland, Canada, etc.), versus the situation faced by the majority of peripheral economies, as in Latin America, including Mexico, during the last decades. The bottom line of this article is to disclose some underlying factors and circumstances that have prevented a reorientation of the prevailing neoliberal strategies in peripheral economies, namely, those socioeconomic factors and political circumstances under which an emerging economy such as Mexico is currently successfully implementing a socially inclusive and sustainable strategy far from the so-called Washington Consensus, vid, Hurt, Stephen R.(May 27, 2020). DOI:https://doi.org/10.56238/sevened2024.037-151